Conceptual Model Cognitive, Affective, Physical, and External Factor for Individual Information Technology Acceptance - Anfazul F. Azizah; Tony Dwi Susanto (Institut Teknologi Sepuluh Nopember, 2015)
Information technology growth provides a lot of opportunity for business and industries. Information technology provide chances to business and industries to improve their ability effectiveness and efficiency. Information technology provide more effective data which can be use to analyze the business process. But many business and industry specially home industry which cannot take the advantage of information technology growth and effect to loss opportunity to built time to market correctly and can predicted market behaviors. There are several factors that affected in decisions making related to the use of information technology are factor cognitive, affective factors, physical factors and external factors that can be analyzed to determine the effect the relationship between the four factors in decision making.